EVALUASI JALUR EVAKUASI DI BAPPEDA ACEH - Muntadhar Abdul Fattah; Mochammad Afifuddin; Abdul Munir (JURNAL TEKNIK SIPIL, 2017)
Abstract: Disaster is an event or the sequence of events which threaten and disrupt the lives and society livelihood which is caused by natural factors or non-natural factors, and human factors which resulting in the emergence of human fatalities, environmental damage, loss of property, and psychological impact. Banda Aceh city is located between two faults (east-north and south-west of the city). The background of geological layout indicates that Banda Aceh city is prone place toward natural disasters such as earthquake, tsunami, and flood. Building in prone disaster areas should be planned according to the standards and applicable regulations so that it can provide security and comfort for building users. Development planning agency at sub- national level (Bappeda) Aceh is one of the government offices which are responsibility toward planning the regional development so that the goals that have been set up can be achieved well. The purpose of this study is assessing the evacuation route feasibility at Bappeda Aceh, knowing the users or employees’ perception about evacuation route at Bappeda Aceh and formulating strategies of disaster prevention management. Data processing method which is used is the analysis of SWOT and AHP.  According to the SWOT analysis showed that Bappeda Aceh should be more focus to the salvation path or disaster evacuation route including Aceh government's willingness to help the budget for completeness disaster management facilities, as well as the implementation of the training / education on disaster reduction.Abstrak: Bencana adalah peristiwa atau rangkaian peristiwa yang mengancam dan mengganggu kehidupan dan penghidupan masyarakat yang disebabkan, baik oleh faktor alam dan/atau faktor non alam maupun faktor manusia sehingga mengakibatkan timbulnya korban jiwa manusia, kerusakan lingkungan, kerugian harta benda, dan dampak psikologis. Kota Banda Aceh terletak diantara dua patahan (sebelah timur-utara dan sebelah barat-selatan kota). Latar belakang letak geologis menunjukkan bahwa Kota Banda Aceh rawan terhadap bencana alam seperti gempa, tsunami dan banjir. Bangunan gedung pada kawasan rawan bencana harus direncanakan sesuai dengan standar-standar dan peraturan yang berlaku sehingga memberikan keamanan dan kenyamanan bagi pengguna bangunan. Badan Perencanaan Pembangunan Daerah (Bappeda) Aceh merupakan salah satu kantor pemerintahan yang bertugas merencanakan pembangunan daerah sehingga sasaran yang diinginkan dapat tercapai dengan baik. Tujuan dari penelitian ini adalah mengkaji kelayakan jalur evakuasi di Kantor Bappeda Aceh, mengetahui persepsi pengguna atau karyawan mengenai jalur evakuasi bencana di Kantor Bappeda Aceh dan merumuskan strategi manajemen penanggulangan resiko bencana di Kantor Bappeda Aceh. Metode pengolahan data yang digunakan adalah analisis SWOT dan AHP. Berdasarkan análisis SWOT  diperoleh bahwa Bapedda Aceh harus lebih fokus kepada jalur keselamatan ataujalur evakuasi bencana termasuk didalamnya kesediaan Pemerintah Aceh untuk membantu anggaran untuk kelengkapan fasilitas penanggulangan bencana, serta adanya pelaksanaan pelatihan/pendidikan mengenai penanggulangan bencana.